ACOUSTIC BIRD REPELLENTS – A BRIEF REVIEW - Matsyura, A. V.; Yakovlev, R. V.; Ulanov, P. N. (Acta Biologica Sibirica, 2016)
The advantages and disadvantages of acoustic bird repellents were considered regards their use in municipal objects. The analysis of their technical features, prices and possible use was performed.